Medication safety program reduces adverse drug events in a community hospital. Issue 3 (2nd June 2005) - Cohen, M M; Kimmel, N L; Benage, M K; Cox, M J; Sanders, N; Spence, D; Chen, J
Abstract : Background: There is widespread interest in improving medication safety, particularly in the hospital setting. Numerous suggestions have been made as to how this should be done, but there is a paucity of data demonstrating the effectiveness of any of the interventions that have been proposed. Objectives: To assess the impact of a wide ranging, community hospital based patient safety program on patient harm as measured by the rate of adverse drug events. Design: An audit of discharged hospital patients was conducted from January 2001 to December 2003. Baseline data were collected for the first 6 months and multiple drug protocols and other interventions were instituted on the nursing units and in the pharmacy department over the subsequent 9 months (transition period). These interventions were largely based on information about medication risks acquired from internal medication event reporting. Each month of the study adverse drug events (ADE) were sought from a random sample of inpatient charts. A trigger tool was used to detect clues to ADEs, the presence of which was confirmed or excluded by detailed manual chart review. The severity of these events was categorized using the classification system of the National Coordinating Council for Medication Error and Reporting and Prevention. Main outcome measures and results: Median ADEs per 1000 doses of medication dispensed declined significantly from 2.04 to 0.65 (p<0.001). Median ADEs per 100 patient days declined significantly from 5.07 to 1.30 (p<0.001). The proportion of inpatients with one or more ADE in the baseline period was 31% and declined threefold (p<0.001). The severity of reported medication events also declined. The number of ADEs associated conclusively with patient harm was 1.67 per total doses delivered in the baseline period and declined eightfold (p<0.001). Conclusion: The implementation of a carefully planned series of low cost interventions focused on high risk medications, driven by information largely from internal event reporting, and designed to improve a hospital's medication safety leads to a significant decrease in patient harm.